Integrating Workplace Learning Concept In The Ministry Of Trade Officials Competency Development: A Business Canvas Model Of Trade Negotiator Training - Hidayati, Ratnaningsih; Rachman, Nadya Megawati; Agustina, Srie (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2023)
The current portrait of Indonesia government officials is not as expected. About a third of Indonesian civil servants have low competence, potential, quality of performance and integrity. In addition, competency development programs that have been running are considered not in accordance with the needs of the organization. This paper aims to provide an overview of the concept of ASN competency development that adopts the learning model at Corporate University, which is to integrate workplace learning as part of government official learning at the Ministry of Trade. The study was conducted using a qualitative approach, by conducting relevant scientific literature studies and mapping the concept into the Business Model Canvas. The results of the study show that there are three values that are expected to be the output of a paradigm shift in developing ASN potential at the Ministry of Trade, namely: (1) The process of transferring knowledge, skills and work attitudes effectively and efficiently without having to leave office assignments; (2) construction and indexation of knowledge through experiential learning; and (3) contributing to problem solving in the workplace.